ANALISIS PENERAPAN GOOD CORPORATE GOVERNANCE DALAM PENGELOLAAN DANA DESA DI DESA SEWUREJO KARANGANYAR - Marita Kusuma Wardani; Ahmad Shofwan Fauzi (Among Makarti, STIE AMA Salatiga, 2019)
Abstract The concept of good governance is used as an institutional framework for strengthening the autonomy of village. The reality is practice of good governance in management practices of more funds are directed to central government, not to public. The purpose of this study was to understand the forms and practices of good governance froms and practices in village fund management pricesses that are viewed from the proses of trasnparansi. Accountabillty and responsiveness. This study uses an interpretive paradigm with a phenomenological approach to explore the implementation of good governance in management of village funds. The study found that implementation of the management of village funds in village sewurejo normatively in accordance with good governance mechanisms even though there are still some weaknesses in the application in field. The policy implication of this research can be used to assess implementation of good governance at the village government agencies special in village governance. Keywords : village fund, good governance, trasnparansi, Accountabillty.